The Effect of Integrated Ovitrap in Reducing The Transovarial Transmission Index in DHF Endemise Areas - Saepudin, Malik; Kasjono, Heru Subaris; Martini, Martini; Setyowati, Eny (Poltekkes Kemenkes Palu, 2024)
Dengue hemorrhagic fever is a health problem in Indonesia. Pontianak City as the city center of West Kalimantan Province has an important role in the spread of dengue fever. An effective integrated model for vector control is needed to reduce the incidence of dengue fever in endemic areas. We carried out an intervention using the integrated CTVVC and SAMT model for 4 weeks in 100 homes as an intervention group. To determine the impact of implementing this model, blood samples were examined from the population and Aedes Spp eggs were collected into 2 groups, namely the intervention group and the control group for 4 weeks, namely 3 weeks. before the intervention and 3 weeks after. The egg samples were then colonized into adult mosquitoes with an average age of 7 days. Next, the analysis was carried out according to the immunocytochemical method of streptavidin biotin peroxidase complex (ISBPC) and Polymerase Chain Reaction Transcription Reaction (PCR). The measurement results show that the DENV transovarial index in the intervention area is lower than in the control area, namely 40% and 50%, as well as the DENV infection index in the population shows that DENV infection is higher compared to the intervention. area, namely 26.47% and 22.50%. However, statistical analysis did not show the effect of the CTVVC-SAMT integration model on DENV transovarial transmission index and DENV infection in the population with P value: 0.66, P value: 0.109. This research succeeded in identifying the DENV-3 type.